Using emoji to ascertain student emotional responses to technology-based human anatomy instruction - Magrum, Shawn M.; Bird, Jaynie; Snow, Ethan L. (Frontiers in Education, 2025)
IntroductionDespite the increase of three-dimensional (3D) technological integration into academia, little consideration has been given to the emotional responses of students to such pedagogy. Both pleasant (high valence/sentiment) and unpleasant (low valence/sentiment) emotions influence the cognitive processes involved in learning, and emotional sentiment can be exemplified by particular emoji.MethodsA survey with 10 facial emoji stratified into three categories (positive, neutral, and negative sentiment) was administered to students completing a human anatomy course with 3D visualization technology (3DVT) and augmented reality (AR) integration. The survey was administered before and after each class session (technology-based learning sessions, non-technology-based learning sessions, and examination sessions) to measure student emotional sentiment. Pre- and post-course questionnaires were also administered to clarify reactions to the technology.ResultsResults indicated that students reported positive and neutral emotions nearly exclusively, although students reported a reduction in emotional sentiment after technology-based learning sessions as compared to after non-technology-based learning sessions (Z = −2.557, p = 0.011). Lower emotional sentiment was associated with the examination sessions as compared to either of the learning session types, and students reported an increase in emotional sentiment after the examination sessions as compared to before the examination sessions (Z = −2.066, p = 0.039).DiscussionThe present study revealed that the 3D technologies elicited primarily neutral or positive emotions, and that the integration of an emoji survey can aid instructors in monitoring student emotional responses to pedagogical interventions.